UPAYA IFC (INDONESIAN FASHION CHAMBER) DALAM MEWUJUDKAN INDONESIA SEBAGAI “THE FASHION MUSLIM CENTER OF THE WORLD 2025” - Rima Sartika Ulfa; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The development of the fashion world continues to increase, starting from technology and media so that various modes and styles as well as clothing are also social symbols so as to provide a cultural identity to someone. Regarding the aim of the study to find out which developments in fashion hijab in Indonesia, find out IFC (Indonesian Fashion Chamber) in realizing Indonesia as the "The Fashion Muslim Center Of The World 2025", and explain how to explore surly Muslim communities export hijab and to learn and explain done by Indonesian Hijab designers in penetrating foreign markets. The research conducted is qualitative research, with the research method used is descriptive research method that is the research method that addresses the objectives in the field then proceed with interpretation of data in order to explain or analyze the problem being sought. Methods this study aimed to describe or explain the events and occurrences that exist at the present time. This method is a method which seeks to collect, collate, interpret the data that was submitted by analyzing these data or analyzes of the phenomenon as well as a method of examining an object, a condition, a system of thought or a class of events in the present. In realizing Indonesia as a fashion hijab center in the world, IFC joined the government in carrying out various kinds of efforts, both internal and external. Starting from improving the quality of the fashion industry, developing and enhancing brands, holding events to improve hijab clothing, participating in trade events, to establish cooperation with Malaysia, Singapore, Hong Kong, holding international events that provide assistance supported by the Indonesian government.Keywords: Export, Fashion Hijab, IFC, The Fashion Muslim Center of The World